2011
DOI: 10.1111/j.1600-0625.2011.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensor materials for the detection of human neutrophil elastase and cathepsin G activity in wound fluid

Abstract: Human neutrophil elastase (HNE) and cathepsin G (CatG) are involved in the pathogenesis of a number of inflammatory disorders. These serine proteinases are released by neutrophils and monocytes in case of infection. Wound infection is a severe complication regarding wound healing causing diagnostic and therapeutic problems. In this study we have shown the potential of HNE and CatG to be used as markers for early detection of infection. Significant differences in HNE and CatG levels in infected and non-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 77 publications
0
74
0
Order By: Relevance
“…Bone marrow-derived stem cell transplantation can also be used for the healing of chronic lower extremity wounds. Hassan et al [190] topically applied a concentrated solution of bone marrow stem cells combined with platelets and fibrin glue in a collagen dressing. After 4 weeks of treatment, diabetic ulcers were totally closed in three patients and significantly reduced in another five patients.…”
Section: Cellulose and Its Derivativesmentioning
confidence: 99%
“…Bone marrow-derived stem cell transplantation can also be used for the healing of chronic lower extremity wounds. Hassan et al [190] topically applied a concentrated solution of bone marrow stem cells combined with platelets and fibrin glue in a collagen dressing. After 4 weeks of treatment, diabetic ulcers were totally closed in three patients and significantly reduced in another five patients.…”
Section: Cellulose and Its Derivativesmentioning
confidence: 99%
“…Some of these approaches are based on the detection of the enzymes present in the medium associated with an inflammatory response of the human body. 15,16,17,18 In different strategies, virulence factors secreted by pathogenic bacteria are targeted for the in situ detection. 19,20,21,22 Zakir Hossain et al 23 reported for instance on a lab-onpaper assay for the rapid and sensitive detection of E. coli in water.…”
Section: Introductionmentioning
confidence: 99%
“…18 Both elastase and cathepsin G are secreted at high levels by activated neutrophils early during an infection; as a result, a recent study has suggested that the activity of these proteases could be used as an early biomarker to detect wound infection. 19 Since both of these proteases are capable of degrading basement membrane proteins, it has been suggested that they could potentially interfere with re-epithelialization and the formation of a new basement membrane in the dermo-epidermal junction by keratinocytes. 20 This idea is supported by a study showing that the elastase inhibitor gramerin accelerates re-epithelialization rates.…”
Section: Neutrophil-derived Proteasesmentioning
confidence: 99%